KAJIAN TEORITIS RANCANGAN BILAH KINCIR ANGIN HORIZONTAL MODIFIKASI NACA 4412, 4415, 23012, DAN 23015 SEBAGAI PENGHASIL ENERGI ALTERNATIF DI MANOKWARI - Rosalina Rosina Mirino; I Gede Deny Arsemaya Partadinova; Aries Astradhani Subgan (Jurnal Natural, 2022)
This research aims to produce a windmill blade design simulation using Airfoil NACA series 4412, 4415, 23012, 23015 and to determine the best type of windmill blade design based on the amount of power generated by the wind speed. The blade design was made using the Qblade v0.91b program based on the NACA 4412, 4415, 23012, and 23015 airfoils with taper and taperless types. Blade design begins with determining blade geometry and continues with blade design performance testing. Wind speed in Manokwari is classified based on the limit of the effective wind occurring in a day, which is 9 hours. The results showed that NACA 4412 and NACA 4415 were better than NACA 23012 and NACA 23015 with the efficiency of each blade reaching 49%. The NACA 4412 series taper produces an average total power per month of 168.38 KW and taperless of 196.93 KW from the average number of occurrences of potential wind speed of 9.35 m/s of 26 days. The NACA 4415 taper blade produces 164.8 KW of power while the taperless blade is 192.73 KW for the same average number of wind potentials. Based on the amount of power generated, the taperless type in the 4412 series is the best blade for wind speed in Manokwari.